2014
DOI: 10.1603/an14054
|View full text |Cite
|
Sign up to set email alerts
|

Biological Parameters ofPodisus nigrispinus(Hemiptera: Pentatomidae) Fed with Different Soybean Insect Pests

Abstract: Biological parameters of Podisus nigrispinus (Dallas) fed with third-instar Lepidoptera larvae of Spodoptera frugiperda J.E. Smith, Spodoptera cosmioides (Walker, 1858), and Anticarsia gemnmtalis (Hiibner, 1818), as well as eggs of Euschistus heros (F" 1798), the brown stink bug, were evaluated. Experiments were performed under controlled conditions (25 ± 1°C; 70 ± 10% relative humidity, and a photoperiod of 16:8 [L:D] h ). P. nigrispinus had good nymphal development with >87% larval survival (viability), as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The number of breeding-pairs formed varied between the different treatments, ranging from at least 5 for the most harmful products to 25 for the control and for more selective products. These pairs were kept in cages for a period of 10 days, during which time the insects presented greater oviposition capacity (DENEZ et al, 2014) to evaluate possible effects on fertility, according to protocols standardized by IOBC, described by Viñuela et al (2000).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of breeding-pairs formed varied between the different treatments, ranging from at least 5 for the most harmful products to 25 for the control and for more selective products. These pairs were kept in cages for a period of 10 days, during which time the insects presented greater oviposition capacity (DENEZ et al, 2014) to evaluate possible effects on fertility, according to protocols standardized by IOBC, described by Viñuela et al (2000).…”
Section: Methodsmentioning
confidence: 99%
“…In natural biological control, the insect predator Podisus nigrispinus (Dallas) (Hemiptera: Pentatomidae) is an important biological control agent in Soybean-IPM because it plays an important role in the control of different lepidopteran pests (TORRES et al, 2006) and has large consumption capacity of other pest species (DENEZ et al, 2014). Despite the importance of biological control, chemical control might still be necessary.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar study, Medeiros et al (2000) reported that nymph development of this predator was shorter when allowed to feed on A. gemmatalis caterpillars reared on an artificial diet (T1) or caterpillars fed soybean plants (T2) or T. molitor larvae (T3) than when allowed to feed on Alabama argillacea Hübner (Lepidoptera: Noctuidae) larvae on cotton plants. Furthermore, the duration for instars II and III of this predator with A. gemmatalis pupae was longer than those fed on Spodoptera frugiperda (Smith & Abbot), Spodoptera cosmioides (Walker) larvae (Lepidoptera: Noctuidae) and eggs of Euschistus heros F. (Hemiptera: Pentatomidae) (Denez et al 2014).…”
Section: Discussionmentioning
confidence: 86%
“…Nymphal viability did not differ statistically between treatments (Table 1). In other studies, the predator reached 89.00% of nymphal viability when fed with D. saccharalis caterpillars (Vacari et al, 2007), 88.60% with Spodoptera cosmioides (Walker, 1858) (Lepidoptera: Noctuidae) (Denez et al, 2014), 64.00% with S. frugiperda (Oliveira et al, 2004b) and 60.00% com Thyrinteina arnobia (Stoll, 1782) (Lepidoptera: Geometridae) (Oliveira et al, 2011). The results obtained in this work demonstrate the adaptation of the predator P. nigrispinus to the prey H. armigera.…”
Section: Biological Aspects Of P Nigrispinus Nymphs With H Armigeramentioning
confidence: 90%